Coronary Microvascular Dysfunction in Patients with Congenital Heart Disease - Vanreusel, Inne; Segers, Vincent F.M.; Craenenbroeck, Emeline V.; Berendoncks, An Van (Current Cardiology Reviews, 2023)
Congenital heart diseases represent a wide range of cardiac malformations. Medical and surgical advances have dramatically increased the survival of patients with congenital heart disease, leading to a continuously growing number of children, adolescents, and adults with congenital heart disease. Nevertheless, congenital heart disease patients have a worse prognosis compared to healthy individuals of similar age. There is substantial overlap in the pathophysiology of congenital heart disease and heart failure induced by other etiologies. Among the pathophysiological changes in heart failure, coronary microvascular dysfunction has recently emerged as a crucial modulator of disease initiation and progression. Similarly, coronary microvascular dysfunction could be important in the pathophysiology of congenital heart diseases as well. For this systematic review, studies on maximal vasodilatory capacity in the coronary microvascular bed in patients with congenital heart disease were searched using the PubMed database. To date, coronary microvascular dysfunction in congenital heart disease patients is incompletely understood because studies on this topic are rare and heterogeneous. The prevalence, extent, and pathophysiological relevance of coronary microvascular dysfunction in congenital heart diseases remain to be elucidated. Herein, we discuss what is currently known about coronary microvascular dysfunction in congenital heart disease and future directions.
Keywords: microcirculation